2022
DOI: 10.1177/2473011421s00048
|View full text |Cite
|
Sign up to set email alerts
|

Declining Trends in Medicare Reimbursement in Orthopaedic Foot and Ankle Surgery

Abstract: Category: Ankle; Ankle Arthritis; Arthroscopy; Bunion; Hindfoot; Lesser Toes; Midfoot/Forefoot; Sports; Trauma; Other Introduction/Purpose: With the increasing complexity of physician reimbursement models, understanding reimbursement trends is crucial to the financial sustainability of orthopaedic practices nationwide. Inflation-adjusted Medicare physician reimbursement for total joint arthroplasty has decreased by approximately 33% from 2000 to 2019. Recent trends in orthopaedic foot and ankle reimbursement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tis trend is consistent with fndings from Levitski (1996) regarding reductions in Medicare reimbursements over time for cardiac surgery [9]. Decreasing Medicare reimbursement rates over time have also been reported in other felds such as neurosurgery (25.8% decline, CAGR −1.66%), general surgery (24.4% decline, CAGR −1.6%), reconstructive plastic surgery (14% decline, CAGR −0.8%), oral maxillofacial surgery (13.4% decline, CAGR −0.88%), orthopedic trauma surgery (30% decline, CAGR −1.5%), reconstructive microsurgery (26.92% decline, CAGR −1.35%), shoulder surgery (26.9% decline), and foot and ankle surgery (30% decline, CAGR −1.5%) [10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Tis trend is consistent with fndings from Levitski (1996) regarding reductions in Medicare reimbursements over time for cardiac surgery [9]. Decreasing Medicare reimbursement rates over time have also been reported in other felds such as neurosurgery (25.8% decline, CAGR −1.66%), general surgery (24.4% decline, CAGR −1.6%), reconstructive plastic surgery (14% decline, CAGR −0.8%), oral maxillofacial surgery (13.4% decline, CAGR −0.88%), orthopedic trauma surgery (30% decline, CAGR −1.5%), reconstructive microsurgery (26.92% decline, CAGR −1.35%), shoulder surgery (26.9% decline), and foot and ankle surgery (30% decline, CAGR −1.5%) [10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have examined the trends in Medicare reimbursement for physicians, with a nearly universal decline in inflation-adjusted compensation for various orthopaedic procedures. 11,18,23,[26][27][28][29][30][31][32] Regarding spine surgery, a recent study by Haglin et al 10 found that all 15 procedures they examined experienced a notable decrease in inflation-adjusted reimbursement, with an average of 33.8% from 2000 to 2021. When doing a subanalysis on temporal trends, the average adjusted reimbursement rate for all procedures decreased by 23.4% from 2000 to 2010 and 15.6% from 2010 to 2021 (P , 0.0001).…”
Section: Ambulatory Surgical Center Trendsmentioning
confidence: 99%